Alteridade e reconhecimento mútuo em Ricoeur - Gubert, Paulo Gilberto (2012)
From a phenomenological perspective, is investigated the ethical concepts of alterity and mutual recognition in the work of Paul Ricoeur. In the first place, it s shown that, after pointing out the central role of the other in the Aristotelian concept of friendship and the second formulation of Kantian s categorical imperative, Ricoeur suggests the practical wisdom as a point of balance between the teleological tendency and deontological. In the second place, based on the phenomenological approach, it is demonstrated that the radical polarization in terms ego and alter ego is invalid insofar that it does not lead the valorization of other's uniqueness. From the relationship between the ethic of respect and sympathy of the phenomenology, results that is necessary situate the historical character and anthropological of the alterity, firmed by the inherent conflicts in the struggle for recognition. Finally, it is evident that the struggle, the violence and the disregard are forms of recognition of someone that deny the alterity and conceal the desire for solitude through his death. As an alternative to the recognition for the struggle, is presented a model of peaceful recognition that is established through the generosity and gratitude, inherent of the dynamics of exchange of gifts.